2020
DOI: 10.1039/c9ra09315j
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of a chemical sensor with PANI-TiO2 nanocomposites

Abstract: The conjugated conducting polyaniline was fabricated onto PANI-TiO2 nanoparticles prepared by microwave-accelerated reaction system for the development an efficient and sensitive electrochemical sensor to protect the environment and healthcare fields in a broad scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The NCZ NCs can be easily seen in the cavity of PANI (Figure 6). The NCZ NCs can be seen on the polymer matrix of PANI in the TEM image of NCZ/PANI NCs [45] . Similar information about average particle size was obtained from TEM images i. e., 10–20 nm for NCZ NCs and 20–30 nm for NCZ/PANI NCs as observed from SEM and XRD techniques.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The NCZ NCs can be easily seen in the cavity of PANI (Figure 6). The NCZ NCs can be seen on the polymer matrix of PANI in the TEM image of NCZ/PANI NCs [45] . Similar information about average particle size was obtained from TEM images i. e., 10–20 nm for NCZ NCs and 20–30 nm for NCZ/PANI NCs as observed from SEM and XRD techniques.…”
Section: Resultssupporting
confidence: 72%
“…The NCZ NCs can be seen on the polymer matrix of PANI in the TEM image of NCZ/PANI NCs. [45] Similar information about average particle size was obtained from TEM images i. e., 10-20 nm for NCZ NCs and 20-30 nm for NCZ/PANI NCs as observed from The corrosion rate (CR) and corrosion inhibition efficiency (CIE) was estimated by the weight loss technique. [46][47][48] Table 2 shows the weight loss (mg), standard deviation (S d ), CR, and CIE shown by NCZ/PANI NCs.…”
Section: Chemistryselectmentioning
confidence: 79%
“…is is due to their chemical stability, conductivity, lightweight nature, and mechanical exibility [12]. Among the conducting polymers, polyaniline is broadly used for its excellent properties, such as excellent conductance, easy preparation, low fabrication cost, environmental friendliness and stability, and its electrochemical redox characteristics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers are attractive materials due to their various functions, from insulators to conductors, while retaining traditional polymers’ mechanical properties and processing qualities. Polyaniline (PANI) is one of the most promising conductive polymers due to its unique physical and electrochemical properties. Current research has revealed its functionalities by fabricating diverse morphologies, composites, colloids, and hydrogels. Different PANI nanostructures have been used in numerous fields, extending from adsorbents, chemical sensors, biosensors, , electrocatalysis, , and supercapacitors to electrode materials for batteries. …”
Section: Introductionmentioning
confidence: 99%